2015
DOI: 10.1016/j.rmed.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-based spatial correlation analysis for ambient air pollution and AECOPD hospitalizations in Jinan, China

Abstract: Ambient air pollution is correlated with AECOPD hospitalizations spatially. A 10 μg/m(3) increase of PM10 at workplace was associated with a 7% (95%CI: [3.3%, 10%]) increase of hospitalizations due to AECOPD in Jinan, 2009. As a spatial data processing tool, GIS has novel and great potential on air pollutants exposure assessment and spatial analysis in AECOPD research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…or by artificial ones (biomass, coal and wood burning, traffi c, including dusty roads, industry, etc.). 2 The measured levels of PM 10 in Pleven in 2012 showed mean yearly level of 45.48 μg/m 3 and 106 days with levels of PM 10 above 50 μg/ m 3 . It makes it one of most polluted cities in the Europe.…”
Section: Levels Of Pm 10mentioning
confidence: 93%
See 2 more Smart Citations
“…or by artificial ones (biomass, coal and wood burning, traffi c, including dusty roads, industry, etc.). 2 The measured levels of PM 10 in Pleven in 2012 showed mean yearly level of 45.48 μg/m 3 and 106 days with levels of PM 10 above 50 μg/ m 3 . It makes it one of most polluted cities in the Europe.…”
Section: Levels Of Pm 10mentioning
confidence: 93%
“…The daily mean concentrations of PM 10 were found to correlate signifi cantly with the daily mean concentrations of NO 2 and SO 2 (ρ 0.34 and ρ 0.49, respectively; p=0.0001). The negative correlations between the daily mean temperature and the daily mean levels of PM 10 , NO 2 and SO 2 were also signifi cant (ρ -0.44, ρ -0.11, and ρ -0.37, respectively; p=0.0001). The daily number of AECOPD correlated with the mean levels of PM 10 in the previous six days (ρ 0.14; p=0.02) and the lower outdoor temperature (ρ -0.2; p=0.001).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have used this method to examine the health effects of air pollutants (Sun et al 2013;Wang et al 2015). Some studies also indicated that the kriging method provided the more accurate exposure estimates and could affect the evaluation of the health effects in an epidemiological study (Son et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars used GIS in their studies. Therefore, many methods including geographically weighted regression [33] and spatial correlation analysis [34] were introduced. Dujardin et al [35] analyzed the impact of territorial structures upon energy consumption in the Wakkoon Region and revealed that some rural settlements characterized by low density show good performance in terms of energy efficiency.…”
Section: Related Studiesmentioning
confidence: 99%